INVENTARISASI DAN IDENTIFIKASI PENYAKIT PADI YANG DISEBABKAN OLEH CENDAWAN DI DESA SUNGAI ITIK KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Erika Kornelia Sari; Tris Haris Ramadhan; Fadjar Rianto (Fakultas Pertanian Universitas Tanjungpura, 2018)
ABSTRACT Rice production in West Kalimantan often fluctuates. This is caused by various factors, one of them are caused by plant pathogen. This study aims was to identify rice disease in Sungai Itik, Sungai Kakap, Kubu Raya Districts. Plant sampling used purposive sampling method which done systematically. Identification of pathogen causes of the disease was done microscopically. The result of identification showed that there are 6 rice diseases such as narrow brown leaf spot, leaf and neck blast , stackburn, black kernel, and sheath rot and sheath blight. The result of disease severity calculations on rice leaves indicate the range of intermediate values 54.81% - 78.51%, rice stem 2.22% - 21.48%, and panicle of rice 56.66% - 71.85%. Keywords : Diseas, Identification, Rice, Severity